Impact of Political Uncertainty on Pakistan Stock Exchange: An Event Study Approach - SULEHRI, Fiaz Ahmad; ALI, Amjad (Journal of Advanced Studies in Finance, 2020)
Pakistan is struggling against many problems; out of which political instability and terrorism are crucial problems. These issues hindered the economic growth of the country as well as the confidence of investors. This study has investigated the impact of political events on Pakistan Stock Exchange. This paper uses a standard event study methodology. Data relating to the stock market index has been collected from the website of Pakistan Stock Exchange and relating to political events has been collected from the newspapers of Business Recorder and DAWN. A total of 18 political events was considered in the study out of which 08 events were coded as positive and other 10 were deemed negative. The first day abnormal return, a five-day cumulative abnormal return and ten-day cumulative return was calculated for all of the events. This study found evidence that political events affected the stock market in Pakistan, but their impact is different considering the economic and political implications of these events. Certain events had the strongest impact on the stock market like Nuclear tests for effective defense, the Supreme Court had revoked the Presidential order and Nawaz Sharif had been reinstated, General elections held in the country and the 14 th amendment because 14 th amendment was related to the elimination of corruption in political parties. Overall, this study laid the foundation to make further explorations into the phenomenon of uncertainty caused by political events in relevance to the stock market in Pakistan.